Effect of Probiotic Supplementation on the Performance of Broiler Chicken - Sabitha Mahaboob Kadari A (Department of Poultry Science, College of Veterinary and Animal Sciences, 2001)
The effects of different levels of pro biotic (Lactobacillus acidophilus, Streptococcus faecium and Yeasacc 1026) supplementation• at 0.025 and 0.05 per cent of the ration on the performance of broiler chicken were evaluated using 144, one-day old, commercial broiler chicks for a period of eight weeks. The birds were divided into three dietary treatment groups viz., standard broiler ration (T 1), standard broiler ration with 0.025 per cent probiotic (T 2) and standard broiler ration with 0.05 per cent probiotic (T3). Standard broiler ration was formulated as per Bureau of Indian Standards (1992) specification for broiler chicken feed. The 0.025 per cent probiotic supplemented birds showed a significantly higher (P<0.05) body weight upto six weeks of age. At the end of eight weeks of age, the 0.05 per cent probiotic fed birds grew faster. The body weight gain was significantly higher in 0.025 per cent probiotic supplemented group upto six weeks of age but was statistically non-significant upto eight weeks of age. The feed intake was not statistically significant throughout the experimental period. Eventhough the feed efficiency was significantly (P<0.01) better in the group fed with 0.025 per cent probiotic at the end of second week, it was statistically non-significant at sixth and eighth weeks of age. The protein efficiency was not significantly different throughout the experimental period. The serum cholesterol levels were significantly (P<0.01) reduced in both the probiotic supplemented groups. The serum